Systemic lupus erythematosus with Fahr’s syndrome: A case report with review of literature - Ramaswamy Subramanian; Shiva Prasad B.N.; Nikhil R.; Mahabaleshwar Mamadapur (Romanian Journal of Rheumatology)
Systemic lupus erythematosus (SLE) is a multisystem disease with autoimmune etiology. The neurological manifestations of lupus are diverse. We introduce a case of a 40-year-old male who presented with constitutional symptoms like low-grade fever, myalgia, and easy fatigability for one month. On examination, he had icterus, hepatosplenomegaly, and spasticity. Lab tests were suggestive of autoimmune hemolytic anemia with ANA positivity and low complements. Diagnosis of SLE was certain. CT brain showed bilateral symmetrical dense radial and punctate calcifications involving bilateral cerebral and cerebellar hemispheres suggestive of Fahr’s syndrome.